Modelling of an integrated standalone streetlamp PV system - Guo, Siyu; Wu, Changsheng; Danner, Manuel; Nobre, Andre; Aberle, Armin G.; Peters, Marius (2015 IEEE 42nd Photovoltaic Specialist Conference, PVSC 2015, 2015)
In this work, the operation of a standalone streetlamp PV system is modeled considering actual outdoor operation conditions. The model integrates all components required in a stand-alone PV system: PV panel, battery, charge controller and load. Electrical characteristics of each component are based on those of a streetlamp PV system, currently tested in Singapore. Using measured irradiance data, the model is able to predict the real-time current flow, battery operating voltage and state of charge. The simulations of the streetlamp system are done using real-measured irradiance data from Singapore and Boston. We find that for a long-term, uninterrupted operation of a standalone PV system actual meteorological conditions need to be considered. The real-time simulation method presented in this work allows better defining the size of the required solar panel and the battery capacity.
CRIS-Team Scopus Importer:2023-03-07
Keywords: battery; PV module; PV system model; stand-alone PV system; streetlamp PV system